Combination of culture and dyeing conditions on cloth color dyed with mixed fungi dyes - Suciatmih Suciatmih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
This study aimed to examine the dyes production of mixed Aspergillus and Paecilomyces on different culture conditions and evaluate the combination between culture and dyeing conditions on cloth color by the fungal dyes. The different media consist of mineral salt glucose (MSG) medium and mineral salt sucrose (MSS) medium were evaluated. Additionally, different culture conditions such as C and N sources, incubation temperature, and pH of the media were evaluated together with variation of dyeing conditions including pH and mordants. The result showed that different culture conditions on media and the combination of those with dyeing conditions produce distinction colors on the fabric. The variation of dyed colors on the fabric was related to the dyes concentration produced by combination treatment of culture condition and dyeing pH. However, the effect was not observed on the combination between culture condition and mordants. Combination of culture and dyeing conditions on cloth color dyed with mixed fungi dyes generated various cloth colors, adding a color variation on textile dyeing.